A combined sodium phosphate and sodium sulfide pretreatment for enhanced enzymatic digestibility and delignification of corn stover. (October 2016) - Qing, Qing; Zhou, Linlin; Guo, Qi; Huang, Meizi; He, Yucai; Wang, Liqun; Zhang, Yue
Graphical abstract: Highlights: A combined Na3 PO4 and Na2 S pretreatment on the digestibility of CS were evaluated. Under the optimal conditions, most carbohydrates were kept in the solids with a high delignification. 91.11% of the original polysaccharides can be converted into fermentable sugars. A strong correlation between lignin removal and the reducing sugar yield was observed. Abstract: Na3 PO4 and Na2 S were employed as efficient alkaline catalysts for the pretreatment of corn stover. To systematically obtain optimal conditions, the effects of critical pretreatment parameters including sodium phosphate concentration (1–4%), sulfidity (0–20%), pretreatment temperature (100–120 °C), and reaction time (20–60 min) on the reducing sugar yield of pretreated substrates were evaluated in a lab-scale using the response surface methodology. Pretreated under the sodium phosphate concentration of 4%, sulfidity of 10%, temperature of 120 °C, and reaction time of 40 min, the reducing sugar yield and glucose yield of the pretreated corn stover achieved 91.11% and 64.01%, respectively, with a moderate enzyme loading of 30 FPU/g substrate. Additionally, a strong correlation (R 2 = 0.971 and R 2 = 0.954) between the delignification and the reducing sugar yield (or glucose yield) was observed by this pretreatment method. These results evidently support that the combined Na3 PO4 -Na2 S pretreatment is an effective and feasible method for processing lignocellulosic biomass.